Diastereodivergent Construction of Octahydrophenanthridinone and Octahydrophenanthridine Cores - Chunzhao Sun; Hiromichi Nishikawa; Tsubasa Inokuma; Ken-ichi Yamada (Molecules)
Diastereodivergent synthesis of octahydrophenanthridinone and octahydrophenanthridine skeletons, structural motifs often found in biologically active natural products, is described. We previously reported a total synthesis of a pancratistatin analog using novel octahydrophenanthridinone construction. In this study, we examined the generality of our method and its extension to octahydrophenanthridine formation. Conjugate addition of diarylcuprates to nitrosocyclohexenes, which were generated in situ from 2-chlorocyclohexanone oximes, provided 2-arylcyclohexanone oximes. Subsequent reduction of the oxime moiety gave cis- and trans-configured amines. Both amines were separately converted into the corresponding octahydrophenanthridinones and octahydrophenanthridines via hexahydrophenanthridine intermediates.